Analisis Yuridis Pengakuan dan Pengesahan Anak Luar Kawin Pasca Putusan Mahkamah Konstitusi Nomor 46/PUU/VIII/2010 (Studi Penetapan Pengadilan Negeri Salatiga Nomor 24/Pdt.P/2021/PN Slt) - Khusna, Erlina Nailal; Widanarti, Herni; Prananda, Rahandy Rizki (Faculty of Law, Diponegoro University, 2023)
One of the legal consequences of marriage is related to the status and position of the child born. If a child is born out of wedlock, then the child is considered a child out of wedlock. A child out of wedlock can be legalized as a legitimate child if the parents submit an application for validation of the child's recognition to the Court. The purpose of this study was to find out the basis for the judge's consideration of the decision of the Salatiga District Court Number 24/Pdt.P/2021/PN Slt after the validity of the Constitutional Court decision Number 46/PUU-VIII/2010 and the legal consequences of the decision of the Salatiga District Court Number 24/Pdt. P/2021/PN Slt on the ratification of children out of wedlock. The research method used in this research is normative juridical legal research which is descriptive-analytical by using secondary data sources and supported by primary data to strengthen the research results. Data analysis was carried out using qualitative analysis methods. The results of the study show that The judge's considerations in determining Number 24/Pdt.P/2021/PN Slt are in accordance with the laws and regulations in force in Indonesia, especially Law Number 24 of 2013 concerning Population Administration and Presidential Regulation Number 96 of 2018 Concerning Requirements and Procedures for Civil Registration and Registration. 2. With the granting of the stipulation, the Petitioner can use a copy of this stipulation to register the registration of the validation of his child's recognition at the Salatiga City Population and Civil Registration Service.